The Position of The National Sharia Council's Fatwas in The Legal System in Indonesia - Sholihin Shobroni (IRDH International Journal of Social Sciences & Humanities, 2024)
One of the functions and role of the Indonesian Ulema Council (MUI) in answering the problems of the ummah and the urgency of Qawa'id Fiqhiyyah in the implementation of fatwas. The method of this research is qualitative research. The results of this study show that: First, the process of establishing the fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) on Islamic banking follows the guidelines or guidelines set by the MUI fatwa commission. Second, the Fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) uses qawaid al-Fiqhiyyah in consideration of its fatwa, especially related to fatwas related to shari'ah banking. Third, the process of legislation and the implementation of fatwas of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) which is binding for shari'ah banking institutions in the form of the process of implementing or pouring fatwas into bank indonesia regulations.